2014
DOI: 10.1523/jneurosci.5309-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-Type Plasminogen Activator Promotes Dendritic Spine Recovery and Improves Neurological Outcome Following Ischemic Stroke

Abstract: Spines are dendritic protrusions that receive most of the excitatory input in the brain. Early after the onset of cerebral ischemia dendritic spines in the peri-infarct cortex are replaced by areas of focal swelling, and their re-emergence from these varicosities is associated with neurological recovery after acute ischemic stroke (AIS). Urokinase-type plasminogen activator (uPA) is a serine proteinase that plays a central role in tissue remodeling via binding to the urokinase plasminogen activator receptor (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 61 publications
3
69
2
1
Order By: Relevance
“…However, the expression of both, the ligand and its receptor, increases in neurons following different forms of injury. These findings are in line with observations by others indicating that the expression of uPAR increases within the first few hours of peripheral nerve [22] , spinal cord [23] and cortical neurons [6,13] injury, and has led to propose that uPAR is a marker of central nervous system damage and a potential therapeutic target to promote neurorepair.…”
Section: Upa-upar Expression In the Central Nervous Systemsupporting
confidence: 90%
See 4 more Smart Citations
“…However, the expression of both, the ligand and its receptor, increases in neurons following different forms of injury. These findings are in line with observations by others indicating that the expression of uPAR increases within the first few hours of peripheral nerve [22] , spinal cord [23] and cortical neurons [6,13] injury, and has led to propose that uPAR is a marker of central nervous system damage and a potential therapeutic target to promote neurorepair.…”
Section: Upa-upar Expression In the Central Nervous Systemsupporting
confidence: 90%
“…Surprisingly, this hypothesis was proven wrong as we failed to detect a difference in the volume of the ischemic lesion between mice genetically deficient in uPA (uPA -/-) and their Wt littermate controls 24 hours after 60 minutes of MCAO. In contrast, we found that compared to Wt littermate controls, uPA -/-and uPAR -/-mice have a protracted recovery in neurological function following MCAO, and that treatment with ruPA or the release of endogenous uPA induces recovery in Wt and uPA -/-, but not in uPAR -/-mice [6,13] . In summary, these data indicate that the expression of uPA and uPAR increase in the sub-acute, recovery stages of ischemic stroke, and suggest that uPA binding to uPAR plays a central role in the process of neurorepair following an acute ischemic injury.…”
Section: Upa and Upar In The Ischemic Braincontrasting
confidence: 60%
See 3 more Smart Citations